2014
DOI: 10.1038/nclimate2339
|View full text |Cite
|
Sign up to set email alerts
|

Changing the intellectual climate

Abstract: Calls for more broad-based, integrated, useful knowledge now abound in the world of global environmental change science. They evidence many scientists’ desire to help humanity confront the momentous biophysical implications of its own actions. But they also reveal a limited conception of social science and virtually ignore the humanities. They thereby endorse a stunted conception of ‘human dimensions’ at a time when the challenges posed by global environmental change are increasing in magnitude, scale and scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
333
0
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 436 publications
(352 citation statements)
references
References 40 publications
1
333
0
18
Order By: Relevance
“…This point is especially important given the imbalance of power still present in transdisciplinary environmental science, particularly regarding climate change (Castree et al, 2014). Calls for useful and integrative knowledge in global change research have coincided with narrow conceptions of social science and poor inclusion of the humanities and stakeholders (Lahsen, 2010;Turnhout et al, 2012;Barnes, 2013;Castree et al, 2014;Carey et al, 2014;Beck et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This point is especially important given the imbalance of power still present in transdisciplinary environmental science, particularly regarding climate change (Castree et al, 2014). Calls for useful and integrative knowledge in global change research have coincided with narrow conceptions of social science and poor inclusion of the humanities and stakeholders (Lahsen, 2010;Turnhout et al, 2012;Barnes, 2013;Castree et al, 2014;Carey et al, 2014;Beck et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Calls for useful and integrative knowledge in global change research have coincided with narrow conceptions of social science and poor inclusion of the humanities and stakeholders (Lahsen, 2010;Turnhout et al, 2012;Barnes, 2013;Castree et al, 2014;Carey et al, 2014;Beck et al, 2014). Making transdisciplinarity work is not only about getting the team and object of concern 'right', but also about attending to how knowledge and power are often unequally available, differentially composed, and fundamental to developing alternative pathways of understanding and response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main concern is that the allure of the 'reductionist' approach in policy-circles can lead to the premature closure of useful options that might otherwise be opened by the 'integrative' approach, in much the same way that some physical climate science circles ignore the contributions of social climate science (see Castree et al, 2014). This analysis has shown that the reductionist approach is problematic because a) at least some of it is insufficiently grounded to justify the support it provides to large investment plans, b) the uncertainties that are veiled by some of these approaches are the very ones that can render resultant policy recommendations ineffective, and c) downplaying of social distributional issues and power asymmetries will tend to favour the wealthy and powerful over the marginalised.…”
Section: The Route To Effective Water Securitymentioning
confidence: 99%